Trpc6 Promotes Doxorubicin-Induced Cardiomyopathy in Male Mice With Pleiotropic Differences Between Males and Females - Norton, Nadine; Bruno, Katelyn A.; Di Florio, Damian N.; Whelan, Emily R.; Hill, Anneliese R.; Morales-Lara, Andrea Carolina; Mease, Anna A.; Sousou, John M.; Malavet, Jose A.; Dorn, Lauren E.; Salomon, Gary R.; Macomb, Logan P.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Doxorubicin is a widely used and effective chemotherapy, but the major limiting side effect is cardiomyopathy which in some patients leads to congestive heart failure. Genetic variants in TRPC6 have been associated with the development of doxorubicin-induced cardiotoxicity, suggesting that TRPC6 may be a therapeutic target for cardioprotection in cancer patients. Methods: Assessment of Trpc6 deficiency to prevent doxorubicin-induced cardiac damage and function was conducted in male and female B6.129 and Trpc6 knock-out mice. Mice were treated with doxorubicin intraperitoneally every other day for a total of 6 injections (4mg/kg/dose, cumulative dose 24mg/kg). Cardiac damage was measured in heart sections by quantification of vacuolation and fibrosis, and in heart tissue by gene expression of Tnni3 and Myh7. Cardiac function was determined by echocardiography. Results: When treated with doxorubicin, male Trpc6-deficient mice showed improvement in markers of cardiac damage with significantly reduced vacuolation, fibrosis and Myh7 expression and increased Tnni3 expression in the heart compared to wild-type controls. Similarly, male Trpc6-deficient mice treated with doxorubicin had improved LVEF, fractional shortening, cardiac output and stroke volume. Female mice were less susceptible to doxorubicin-induced cardiac damage and functional changes than males, but Trpc6-deficient females had improved vacuolation with doxorubicin treatment. Sex differences were observed in wild-type and Trpc6-deficient mice in body-weight and expression of Trpc1, Trpc3 and Rcan1 in response to doxorubicin. Conclusions: Trpc6 promotes cardiac damage following treatment with doxorubicin resulting in cardiomyopathy in male mice. Female mice are less susceptible to cardiotoxicity with more robust ability to modulate other Trpc channels and Rcan1 expression.